Nature relatedness in student teachers, perceived competence and willingness to teach outdoors: an empirical study. Issue 3 (2nd July 2020) - Barrable, Alexia; Lakin, Liz
ABSTRACT: Despite a drive towards more learning outside the classroom, teachers' confidence to teach outdoors has been identified as a barrier to regular and positive outdoor experiences. Initial Teacher Education (ITE) has been seen as one of the ways to increase teachers' confidence, yet such provision is variable and has not been studied extensively. In this study, we explore how a practical outdoor session can increase motivation to teach outdoors. Moreover, using a Self-Determination Theory framework we hypothesise that increased nature relatedness would be associated with higher perceived competence and willingness to teach outdoors. Forty-nine ITE students took part in the outdoor session, and responded to pre- and post-measures of nature relatedness, perceived competence and willingness to teach outdoors. Results suggest a positive correlation between nature relatedness and both perceived competence and willingness to undertake outdoor sessions. Moreover, nature relatedness was significantly higher after the outdoor environmental education session.